Control of Raw Pork Liver Sausage Production Can Reduce the Prevalence of HEV Infection - Paolo Ripellino; Enea Pianezzi; Gladys Martinetti; Cinzia Zehnder; Barbara Mathis; Petra Giannini; Nicola Forrer; Giorgio Merlani; Harry R. Dalton; Orlando Petrini; Florian Bihl; Stefano Fontana; et al. (Pathogens, 2021)
After an acute hepatitis E (HEV) outbreak in Southern Switzerland, in January 2017 the local public health authorities started an active program of food chain control and public education. In this retrospective study, we analysed all laboratory-confirmed acute cases of HEV infection diagnosed between 2014 and 2020. In the period before the public health intervention, the number of cases increased steadily from 2014 (4 of 40 tests, 10%) reaching a peak in the last quarter of 2016 (42 of 285 tests, 14.7 %). Afterwards, the number of positive cases decreased steadily, reaching its lowest value (0.3%) in the second quarter of 2019. There was a statistically significant difference between the frequency of positive cases and period of testing, i.e., before and after the introduction of the public health interventions. Our study shows that active public health measures to control sausages containing raw pork liver can reduce the prevalence of HEV infection.